2020
DOI: 10.1364/optica.396408
|View full text |Cite
|
Sign up to set email alerts
|

Doubly resonant second-harmonic generation of a vortex beam from a bound state in the continuum

Abstract: Second-harmonic generation in nonlinear materials can be greatly enhanced by realizing doubly resonant cavities with high quality factors. However, fulfilling such doubly resonant condition in photonic crystal (PhC) slab cavities is a long-standing challenge, because of the difficulty in engineering photonic bandgaps around both frequencies. Here, by implementing a second-harmonic bound state in the continuum (BIC) and confining it with a heterostructure design, we show the first doubly resonant PhC slab cavit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…a BIC [6]. This approach has also been recently shown to experimentally enhance SHG efficiency in GaN PhC cavities [7]. Here we show that the above strategy can be further generalized and automated, and it can be applied to an arbitrary material platform.…”
Section: B Design Proceduresmentioning
confidence: 75%
See 1 more Smart Citation
“…a BIC [6]. This approach has also been recently shown to experimentally enhance SHG efficiency in GaN PhC cavities [7]. Here we show that the above strategy can be further generalized and automated, and it can be applied to an arbitrary material platform.…”
Section: B Design Proceduresmentioning
confidence: 75%
“…Recently, a novel approach based on the so-called bound-states in the continuum (BIC) has been proposed [6], overcoming the aforementioned obstacle. This strategy has later been shown to be practically effective by realizing doubly resonant SH generation in a III-V semiconductor PhC cavity [7]. The BICs are particular states that stay confined despite the fact they lie above the light line, i.e., their dispersion falls within the continuum of radiative modes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Such states are now called bound states in the continuum (BICs) and they have recently attracted enormous attention in photonics. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] BICs represent spatially localized states with vanishing radiation despite their energy embedded in the continuum spectrum of the environment. Fundamentally, BICs originate from destructive interference, when two or more waves superpose to completely suppress radiative losses.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the presence of topological edge states could enhance the harmonic generation based on robustness of the local field enhancement [32][33][34][35][36][37]. One of the main limiting factors for high conversion efficiencies is the Q factors of the resonant modes of the devices [38][39][40][41][42]. Essentially, SPTIs with tightly localized corner states could be deemed as topology-protected resonant cavities with high Q factors [21], thus providing a promising platform for improving the harmonic generation efficiency.…”
Section: Introductionmentioning
confidence: 99%